Retrospeksi Konsepsi Demokrasi Pancasila Dalam Menghadapi Tantangan Globalisasi - Dede Sri Kartini (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2011)
If the wave of globalization may inspire democratic understanding and its implementation in Indonesia, then the Pancasila Democracy which has similar meaning with the broad definition of democracy will bring advantages for political, economic, and social condition. In the contemporary era, democracy that has been always elaborated was the democracy that originally came from the West. It has also been socialized only in its narrow definition; therefore, democracy is only commonly understood as political democracy. However, in broad definition of democracy – called by Held as democracy autonomy - the State has an obligation to guarantee that people have easy access not only to political affairs but also to social and economic ones. For that reason, it is necessary to examine several regional elections that have been held successfully. Democracy was not violated when provincial election budget was used for facilitating people to access their neglected economic and social rights. It is difficult to establish democracy in the midst of extreme poverty. New order had made its own interpretation to Pancasila Democracy, and nowadays a more suitable interpretation needs to be made through normative and pragmatic studies.